Lack of Neurotrophin-4 causes selective structural and chemical deficits in sympathetic ganglia and their preganglionic innervation - Roosen, Alexander; Schober, Andreas; Strelau, Jens; Böttner, Martina; Faulhaber, Jörg; Bendner, Gerald; McIlwrath, Sabrina L.; Seller, Horst; Ehmke, Heimo; Lewin, Gary R.; Unsicker, Klaus (The journal of neuroscience, 2001)
Neurotrophin-4 (NT-4) is perhaps the still most enigmatic member of the neurotrophin family. We show here that NT-4 is expressed in neurons of paravertebral and prevertebral sympathetic ganglia, i.e., the superior cervical (SCG), stellate (SG), and celiac (CG) ganglion. Mice deficient for NT-4 showed a significant reduction (20-30%) of preganglionic sympathetic neurons in the intermediolateral column (IML) of the thoracic spinal cord. In contrast, neuron numbers in the SCG, SG, and CG were unchanged. Numbers of axons in the thoracic sympathetic trunk (TST) connecting the SG with lower paravertebral ganglia were also reduced, whereas axon numbers in the cervical sympathetic trunk (CST) were unaltered. Axon losses in the TST were paralleled by losses of synaptic terminals on SG neurons visualized by electron microscopy. Furthermore, immunoreactivity for the synaptic vesicle antigen SV2 was clearly reduced in the SG and CG. Levels of catecholamines and tyrosine hydroxylase immunoreactivity were dramatically reduced in the SG and the CG but not in the SCG. Despite this severe phenotype in the sympathetic system, blood pressure levels were not reduced and displayed a pattern more typical of deficits in baroreceptor afferents. Numbers of IML neurons were unaltered at postnatal day 4, suggesting a postnatal requirement for their maintenance. In light of these and previous data, we hypothesize that NT-4 provided by postganglionic sympathetic neurons is required for establishing and/or maintaining synapses of IML neurons on postganglionic cells. Impairment of synaptic connectivity may consequently reduce impulse flow, causing a reduction in transmitter synthesis in postganglionic neurons.